Mitochondria-Targeted Nanomedicine for Enhanced Efficacy of Cancer Therapy - Gao, Yan; Tong, Haibei; Li, Jialiang; Li, Jiachen; Huang, Di; Shi, Jisen; Xia, Bing (Frontiers in Bioengineering and Biotechnology, 2021)
Nanomedicine have been designed and developed to deliver anticancer drugs or exert anticancer therapy more selectively to tumor sites. Recent investigations have gone beyond delivering drug to tumor tissues or cells, but to intracellular compartments for amplified therapy efficacy. Mitochondria are attractive targets for cancer treatment due to their important function for cells and close relation to tumor occurrence and metastasis. Accordingly, multifunctional nanoplatforms have been constructed for cancer therapy with the modification of a variety of mitochondriotropic ligands, to trigger the mitochondria-mediated apoptosis of tumor cells. On this basis, various cancer therapeutic modalities based on mitochondria-targeted nanomedicines are developed by strategies of damaging mitochondria DNA (mtDNA), increasing reactive oxygen species (ROS), disturbing respiratory chain and redox balance. Herein, in this review, we highlight mitochondria-targeted cancer therapies enabling by nanoplatforms including chemotherapy, photothermal therapy (PTT), photodynamic therapy (PDT), chemodynamic therapy (CDT), sonodynamic therapy (SDT), radiodynamic therapy (RDT) and combined immunotherapy, as well as ongoing challenges.